SPE Asia Pacific Oil and Gas Conference and Exhibition 2018
DOI: 10.2118/191933-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Predict Lost Circulation in the Rumaila Field, Iraq

Abstract: Lost circulation costs are a significant expense in drilling oil and gas wells. Drilling anywhere in the Rumaila field, one the world's largest oilfields, requires penetrating the Dammam formation, which is notorious for lost circulation issues and thus a great source of information on lost circulation events. This paper presents a new, more precise model to predict lost circulation volumes, ECD and ROP in the Dammam formation. A larger data set, more systematic statistical approach, and a machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Lost circulation estimation is a limited topic in the literature; only a few papers were published about this topic. Some shortcomings were identified in the previous work as follows [34,36,[39][40][41][42]]:…”
Section: To Prohibit the Development Of New Fractures That Maymentioning
confidence: 99%
See 1 more Smart Citation
“…Lost circulation estimation is a limited topic in the literature; only a few papers were published about this topic. Some shortcomings were identified in the previous work as follows [34,36,[39][40][41][42]]:…”
Section: To Prohibit the Development Of New Fractures That Maymentioning
confidence: 99%
“…The data went through processing steps where all outliers, errors, white spaces were removed [43]. Input data were selected based on previous statistical and sensitivity analysis studies conducted that showed the most influential parameters on mud loss as well as experts' opinions [39,41]. Table 2 shows the parameters used to create the models and a summary of statistics for both induced and natural fractures.…”
Section: To Prohibit the Development Of New Fractures That Maymentioning
confidence: 99%
“…Abbas [10] established a loss rate prediction model based on artificial neural network, analyzed the relationship between loss rate and drilling parameters, and controlled drilling parameters can effectively prevent drilling fluid loss. Al-Hameedi [11] conducted in-depth statistical analysis of more than 500 wells in the Rumaila oilfield, proposed a model for predicting loss in the Dammam formation, and proposed a model for optimizing drilling operations. Sabah [12] collected a large amount of data from 61 wells recently drilled in Iran's Marun oilfield, and established artificial neural network, decision tree, adaptive neural-fuzzy inference system, and genetic algorithm-multilayer perception model to quantitatively predict lost circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of circulation increases the nonproductive time spent on mitigating the losses [6], besides increasing the total drilling cost due to loss of drilling mud, which represents, in some cases, 40% of the total cost. The oil and gas industry reported more than $12 billion in the cost of drilling materials and fluids in 2018 [7]. Loss of circulation leads to poor hole cleaning due to the reduction of mud level in the borehole, which decreases its ability to transfer the cutting outside the wellbore [8].…”
Section: Introductionmentioning
confidence: 99%